The problematic on the effectiveness of the legal business null: A critical essay in homage to José León Barandiarán - Ninamancco Córdova, Fort (2018)
The contractual law workers have repeatedly stated that José León Barandiarán “was not only the finest and prolific pen of civil law of the time, but also lived passionately teaching ... and that it is impossible to give notice of such a widespread work, analyzed and influential as that of Leon Barandiarán. “ One subject, where the influence of Leon Barandiarán is presented to us as particularly influential, is the one related to the consequences of nullity. And it is that reviewing the main texts that touch on this matter, as well as sentences issued by the highest national judiciary, you can see that they have not deviated from the doctrine that the teacher taught. However, a new doctrine has been spreading for some years, which raises the need for a new approach to nullity and, as a result, it is analyzed in terms of other considerations, which are substantially different from the fundamental lines that several decades ago Leon Barandiarán.